2016
DOI: 10.7863/ultra.15.12013
|View full text |Cite
|
Sign up to set email alerts
|

Normal Intracranial Translucency Values During the First Trimester of Gestation in a Latin American Population

Abstract: We present normal intracranial translucency values in the first trimester of single gestations with live fetuses in a Latin American population. These values are similar to those described in other populations. The intracranial translucency value was linearly correlated with crown-rump length in fetuses between gestational ages of 11 weeks and 13 weeks 6 days, which is consistent with previous publications, although these data cannot be interpreted independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
2
2
2
1
Order By: Relevance
“…[11] In our study, we showed that the IT diameter increased linearly with increasing CRL, which was consistent with the previous reports. [6,12,13,19] A weak positive correlation was found between increasing CRL and IT in some studies like our study, [11,17] but high correlation was noted in other studies. [6,19] The main difference in our report was the higher sample size than previous reports.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…[11] In our study, we showed that the IT diameter increased linearly with increasing CRL, which was consistent with the previous reports. [6,12,13,19] A weak positive correlation was found between increasing CRL and IT in some studies like our study, [11,17] but high correlation was noted in other studies. [6,19] The main difference in our report was the higher sample size than previous reports.…”
Section: Discussioncontrasting
confidence: 43%
“…[6,12,13,19] A weak positive correlation was found between increasing CRL and IT in some studies like our study, [11,17] but high correlation was noted in other studies. [6,19] The main difference in our report was the higher sample size than previous reports.…”
Section: Discussioncontrasting
confidence: 43%
“…In 2016, Molina-Giraldo et al established a nomogram for the IT in a Latin-American population. [11] They reported a median IT of 1.7 mm (interquartile range, 1.42-.2 mm) in fetuses with a CRL between 45 and 84 mm, which is the measurement used to determine IT presence or absence.…”
Section: Discussionmentioning
confidence: 99%
“…1520 fetüsü değerlendirilmiş, CRL ortalamasını 65 mm (45-84 mm), IT ortalamasını 1.7 mm (0.7-3.4 mm) olarak hesaplamışlardır. Çalışmamızdakine benzer olarak IT ile gestasyonel hafta arasında lineer ve pozitif bir korelasyon saptanmıştır (IT=0,043xC-RL-0,815) [17]. Adiego ve ark.…”
Section: Discussionunclassified